Exploitation and the impact of not regulating its provisions in the UAE Civil Transactions Law - Al-Lahibi, Saleh Ahmed (Journal of Legal and Political Studies, 2015)
The UAE Civil Transactions Law No. 5 of 1985 was clearly influenced by the Jordanian civil law as its historical source. Thus, the disadvantages of the will were only three defects: coercion, error and gross injustice if it was caused by delinquency, making the contract associated with coercion suspended, Mistake, or gross injustice resulting from the breach of an unnecessary contract. However, the question remains as to the fate of the contract if it is the result of the exploitation of one of the contractors to the other contractor, so that this exploitation resulted in gross injustice (non-parity), that this situation is very practical in fact, as if marrying the older wife of a young woman So she will be able to exploit his wife's love for him and dictate to her what he wants from the contracts, and this is exploitation (fancy) and may be exploitation (exploitation of urgent need) does not live up to To the necessity but the need, such as putting a person in his boat in the water and then need to save him If a person is required to rescue, but after an agreement to sell the boat, he agrees to this needy, he becomes in a situation exploited for the need (ie Mgbon), what is the fate of these contracts in UAE laws, hence the problem of research.
Keywords: Civil Transactions; coercion; error; Contract